Rancang Bangun Aplikasi Absensi Kepegawaian Menggunakan Metode Geolocation : (Studi Kasus: Puskesmas - Tarusan, Pesisir Selatan) - Engla Pabuser; Zulhendra Zulhendra; Syafrijon Syafrijon; Resmidarni Resmidarni (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The attendance system is an important aspect of personnel management that affects the effectiveness and efficiency of an institution's operations. Puskesmas Tarusan in Pesisir Selatan Regency still uses a manual attendance system that is vulnerable to data inaccuracies, real-time tracking difficulties, and potential fraud such as leaving attendance. To overcome this problem, this research aims to design a geolocation-based attendance application that can improve the accuracy of employee attendance recording and reduce the potential for abuse of the attendance system. This application uses a GPS-based geolocation method that allows attendance recording to only be done at a predetermined work location. By utilising this technology, attendance recording becomes more accurate, transparent, and can be monitored in real-time. This application was developed using the Unified Modelling Language (UML) approach for system design and using mobile-based technology to be easily accessed by employees. The test results show that this system is able to improve the accuracy of recording employee attendance and reduce the potential for fraud in attendance. In addition, this application provides convenience for management in monitoring employee attendance efficiently. With the implementation of this system, it is expected that Puskesmas Tarusan can improve transparency, accountability, and effectiveness in personnel management.